Are you really doing 'codesign'? Critical reflections when working with vulnerable populations. Issue 11 (3rd November 2020) - Moll, Sandra; Wyndham-West, Michelle; Mulvale, Gillian; Park, Sean; Buettgen, Alexis; Phoenix, Michelle; Fleisig, Robert; Bruce, Emma
Abstract : 'Codesign' and associated terms such as 'coproduction' or 'patient engagement', are increasingly common in the health research literature, due to an increased emphasis on the importance of ensuring that research related to service/systems development is meaningful to end-users. However, there continues to be a lack of clarity regarding the key principles and practices of codesign, and wide variation in the extent to which service users are meaningfully engaged in the process. These issues are particularly acute when end-users include populations who have significant health and healthcare disparities that are linked to a range of intersecting vulnerabilities (eg, poverty, language barriers, age, disability, minority status, stigmatised conditions). The purpose of this paper is to prompt critical reflection on the nature of codesign research with vulnerable populations, including key issues to consider in the initial planning phases, the implementation process, and final outputs. Risks and tensions will be identified in each phase of the process, followed by a tool to foster reflexivity in codesign processes to address these issues.